APPLICABILITY OF COMMUNITY THERAPY IN HIGH SERTÃO PARAIBA (Fiep Bulletin - online, 2014)
Emerging as a new technology insertion programs in care and support to public health, the community therapy, or in any age or social group, brings a great alternative to the quality of existence of each. This article aimed to: Present the community therapy as a strategy of therapeutic action, and in a specific way: Demonstrate actions taken in community care; Understand the operation of community therapy; Presenting the contributions of community care in the lives of participants. With this approach, it was seen that people, regardless of age or gender, have higher complication and stress in their lives and as a strategy of action to combat this, personal empowerment. We conclude that people confuse what is stress, but feel that something afflict them, and above all, realize how empowering yourself can result in better quality of life.
Keywords: Therapy; empowerment; strategies; difficulties